Longitudinal Evaluation of Myocardial Fatty Acid and Glucose Metabolism in Fasted and Nonfasted Spontaneously Hypertensive Rats Using MicroPET/CT - Jennifer S. Huber PhD; Andrew M. Hernandez PhD; Mustafa Janabi PhD; James P. O’Neil PhD; Kathleen M. Brennan DVM; Stephanie T. Murphy BS; Youngho Seo PhD; Grant T. Gullberg PhD (Molecular Imaging)
Using longitudinal micro positron emission tomography (microPET)/computed tomography (CT) studies, we quantified changes in myocardial metabolism and perfusion in spontaneously hypertensive rats (SHRs), a model of left ventricular hypertrophy (LVH). Fatty acid and glucose metabolism were quantified in the hearts of SHRs and Wistar-Kyoto (WKY) normotensive rats using long-chain fatty acid analog 18 F-fluoro-6-thia heptadecanoic acid ( 18 F-FTHA) and glucose analog 18 F-fluorodeoxyglucose ( 18 F-FDG) under normal or fasting conditions. We also used 18 F-fluorodihydrorotenol ( 18 F-FDHROL) to investigate perfusion in their hearts without fasting. Rats were imaged at 4 or 5 times over their life cycle. Compartment modeling was used to estimate the rate constants for the radiotracers. Blood samples were obtained and analyzed for glucose and free fatty acid concentrations. SHRs demonstrated no significant difference in 18 F-FDHROL wash-in rate constant ( P = .1) and distribution volume ( P = .1), significantly higher 18 F-FDG myocardial influx rate constant ( P = 4×10 −8 ), and significantly lower 18 F-FTHA myocardial influx rate constant ( P = .007) than WKYs during the 2009-2010 study without fasting. SHRs demonstrated a significantly higher 18 F-FDHROL wash-in rate constant ( P = 5×10 −6 ) and distribution volume ( P = 3×10 −8 ), significantly higher 18 F-FDG myocardial influx rate constant ( P = 3×10 −8 ), and a higher trend of 18 F-FTHA myocardial influx rate constant (not significant, P = .1) than WKYs during the 2011–2012 study with fasting. Changes in glucose plasma concentrations were generally negatively correlated with corresponding radiotracer influx rate constant changes. The study indicates a switch from preferred fatty acid metabolism to increased glucose metabolism with hypertrophy. Increased perfusion during the 2011-2012 study may be indicative of increased aerobic metabolism in the SHR model of LVH.